Corporate social responsibility in buyer-supplier relationships : is it beneficial for top-tier suppliers to market their capability to ensure a responsible supply chain? - T Leppelt; K Foerstl; E Hartmann (The Retail and Marketing Review, 2014)
This study assesses how top-tier suppliers market their capabilities to ensure a responsible upstream sup- ply chain to their downstream buyers, and how the marketing of corporate social responsibility (CSR)- related supply management practices affects the reputation of top-tier suppliers in business-to-business (B2B) markets. In a crossfunctional multiple-case study involving marketing, purchasing, and sustainability executives of five supplier organizations in Central Europe, we explored four distinct approaches for marketing superior CSR management abilities in B2B markets that potentially foster long-term comparative advantages: (1) Fact-based communication of measurable CSR capabilities, (2) targeting of indirect customers and influencers, (3) marketing through education, and (4) marketing of CSR as a service. More- over, our inductive results provide evidence that the effective marketing of CSR capabilities enhances a supplier’s reputation only if it sends consistent signals to the market. Therefore, a close integration of marketing and purchasing is crucial for achieving signaling consistency. Building on an established frame- work of purchasing-marketing integration in the particular context of CSR we developed a cross- functional theory on the link between marketing, supply chain alignment and reputation, which is expressed in four sets of testable research propositions.